Electronic medical record system-based teleconsultations in pediatric surgery: An initiative from a tertiary care public-funded hospital in North India to alleviate the COVID-19 imposed hospital visit restrictions - Sachit Anand; Anjan Kumar Dhua; Apoorv Singh; Nellai Krishnan Subramonian; Ajay Verma; Vishesh Jain; Devendra Kumar Yadav; Aparajita Mitra; Sandeep Agarwala; Prabudh Goel; Minu Bajpai (Wolters Kluwer Medknow Publications, 2022)
Background: There has been a dramatic effect of the coronavirus disease 2019 pandemic on the daily health-care services. The era of physical consultations is slowly being replaced with teleconsultation, and this current pandemic has tipped the scales further. This study highlights the preliminary experience in providing teleconsultation to pediatric surgical patients at a tertiary care hospital in north India. Materials and Methods: A retrospective analysis of the electronic medical record system records of the patients undergoing teleconsultation at the authors' department between the June 26, 2020 and the September 26, 2020 was performed. The data were categorized on the basis of the type of consultation (urgent, semi-urgent, or routine) and the type of intervention. A comparison with the data from the corresponding months of 2019 was also performed. Results: A total of 261 teleconsultations were conducted during the study period, with a success rate of 69% (181/261). Of these, 96% (171/178) were follow-up patients and 56% (99/178) presented with genitourinary complaints. After triaging, only 10% (18/178) of the patients required urgent medical/surgical attention. Conclusion: In the current as well as postpandemic phase, teleconsultation can act as a potent triaging tool and can help in better utilization of resources alongside helping in the maintenance of social distancing by decreasing the number of physical visits to the hospital.